Conflicting institutional logics as a safe space for collaboration: Action research in a reforestation NGO - Simon J.D. SCHILLEBEECKX, (Institutional Knowledge at Singapore Management University, 2022)
Climate change is the defining issue of our time. Taking urgent action to combat climate change and its impacts (Sustainable Development Goal 13) is one of the most wicked problems governments, companies, and civil society have ever had to solve (Reinecke & Ansari, 2016). The path to solving the climate crisis is reasonably well defined but the road ahead is treacherous. We need to decarbonize the economy so that we can decouple growth from carbon emissions. This requires massive investments in clean energy, a radical rethink of the food production system, and innovations in aviation and primary extractive industries to reduce their environmental impact. However, all this will not be enough. We also need to extract carbon from the atmosphere to counteract many of the already devastating effects of climate change currently underway. The famous “Crowther report” (Bastin et al., 2019), highlighted the enormous potential of tackling climate change through a simple yet effective deployment of a natural technology: reforestation.